Staying alive while living the life: adversity, strength, and resilience in the lives of homeless youth - MacDonald, Sue-Ann (Fernwood Publishing, 2018)
"In Staying Alive While Living the Life, Sue-Ann MacDonald and Benjamin Roebuck unpack the realities of living on the streets from the perspective of homeless youth. While much is written about at-risk youth, most literature on youth homelessness reduces their lives to flattened images with little room for the diverse, complex and individual nature of their experiences. Challenging the dominant youth-at-risk conversation by putting forward a framework of survival and resilience, MacDonald and Roebuck illustrate the ways that young people who experience homelessness demonstrate tremendous resilience when facing adversity, social exclusion and various forms of oppression."--